Burden of carotid artery atherosclerosis in Chinese adults: Implications for future risk of cardiovascular diseases. (April 2017) - Clarke, Robert; Du, Huaidong; Kurmi, Om; Parish, Sarah; Yang, Meng; Arnold, Matthew; Guo, Yu; Bian, Zheng; Wang, Liang; Chen, Yuexin; Meijer, Rudy; Sansome, Sam; et al.
Background: Population-based studies of ultrasound measures of carotid atherosclerosis are informative about future risks of cardiovascular disease. Design: Cross-sectional studies of carotid artery atherosclerosis in 24, 822 Chinese adults from the China Kadoorie Biobank and 2579 Europeans from the UK Biobank. Methods: Mean intima-media thickness of the common carotid arteries and presence of carotid artery plaque were examined in the China Kadoorie Biobank study. The carotid intima-media thickness (cIMT) findings in Chinese (mean age 59 years) were compared with a European population (mean age 62 years). Results: Overall, the mean cIMT in Chinese was 0.70 mm (SD 0.16) and increased with age by 0.08 mm (SE 0.008) per 10-years older age. About 31% of the Chinese had carotid plaques and the prevalence varied 10-fold with age (6% at 40–49 to 63% at 70–89 years) and four-fold by region (range, 14%–57%). After adjustment for age, sex and region, plaque prevalence was higher in smokers than in non-smokers (36% vs . 28%) and two-fold higher in individuals with systolic blood pressure ≥160 mmHg than those with systolic blood pressure <120 mmHg (44% vs . 22%) in the China Kadoorie Biobank study. Mean cIMT was similar in the younger Chinese and European adults, but increased more steeply with age in the Chinese ( p = 0.002). Conclusions: About one-third of Chinese adults had carotid plaques. The rate of progression of carotid atherosclerosis with age was more extreme in the Chinese compared with the European population, highlighting the need for more intensive strategies for cardiovascular disease prevention in China.